2021
DOI: 10.1051/0004-6361/202140687
|View full text |Cite
|
Sign up to set email alerts
|

Galactic spiral structure revealed byGaiaEDR3

Abstract: Using the astrometry and integrated photometry from the Gaia Early Data Release 3, we map the density variations in the distribution of young upper main sequence (UMS) stars, open clusters, and classical Cepheids in the Galactic disc within several kiloparsecs of the Sun. We derive maps of relative over- and under-dense regions for UMS stars in the Galactic disc using both bivariate kernel density estimators and wavelet transformations. The resulting overdensity maps exhibit large-scale arches that extend in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
108
0
6

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(128 citation statements)
references
References 76 publications
14
108
0
6
Order By: Relevance
“…The structure of the galaxy as revealed by its young stellar components, in particular the kinematics, dynamics, and nature of the Galactic spiral arms. Zari et al (2021) demonstrated that the structure of the Milky Way as traced with young OB-type stars is not necessarily the same as deduced from observations of red giants, from analysis of the distribution of dust in the galaxy, or from the distributions of Cepheids and/or masers (see also Poggio et al 2021). The authors found that the distribution of OBA-type stars in the plane is highly structured, with pronounced over-and underdensities, and conclude that young stars in the galaxy are not neatly organized into distinct spiral arms.…”
Section: Intermediate-to High-mass Oba(f)-type Starsmentioning
confidence: 94%
“…The structure of the galaxy as revealed by its young stellar components, in particular the kinematics, dynamics, and nature of the Galactic spiral arms. Zari et al (2021) demonstrated that the structure of the Milky Way as traced with young OB-type stars is not necessarily the same as deduced from observations of red giants, from analysis of the distribution of dust in the galaxy, or from the distributions of Cepheids and/or masers (see also Poggio et al 2021). The authors found that the distribution of OBA-type stars in the plane is highly structured, with pronounced over-and underdensities, and conclude that young stars in the galaxy are not neatly organized into distinct spiral arms.…”
Section: Intermediate-to High-mass Oba(f)-type Starsmentioning
confidence: 94%
“…8, lower panels). On top of this, the faint tail of the P1 and most of P5 sample probe even larger distances (up to d 1000 pc), where the spiral structure of the Milky Way starts to be discernible (Miyachi et al 2019;Poggio et al 2021) and the basic assumption of spatial homogeneity breaks.…”
Section: The "Coarse" Grid: Checking the Requirementsmentioning
confidence: 98%
“…To determine the most likely locations for individual PeVatrons in the outer Galaxy, we briefly review in this section the structure of the Milky Way disk and outline the model we use in the calculations of the subsequent sections. The Milky Way is a four-armed barred spiral galaxy [7,8]. The Sun is located at the distance D = 8.15±0.15 kpc [9] from the Galactic Center, in the immediate vicinity of the Orion -or "Local"-arm, which lies between the Sun and the Perseus arm, see Fig.…”
Section: Possible Source Locations In the Outer Milky Way Diskmentioning
confidence: 99%